Performance Evaluation of Equity Oriented Growth and Dividend Funds of Mutual Funds in India : An Application of Risk – Adjusted Theoretical Parameters - Gowri, M.; Deo, Malabika (Indian Journal of Finance, 2016)
This study attempted to evaluate the performance of fund of funds on the basis of risk-adjusted methods. The performance of fund of funds were compared with the risk free returns as well as the benchmark index (BSE 100), which was taken as the proxy for the market returns. Samples were collected from the AMFI websites and respective AMC websites from April 1, 2007 to March 31, 2014 and the returns were calculated from the respective schemes' NAV price. The methods used in the study is risk adjusted tools of Sharpe ratio, Treynor ratio, and Jensen alpha. An analysis performed on the sample of equity oriented fund of mutual funds showed that all the fund of funds in the sample earned negative returns in excess of the risk free rate of return offered by 91 days treasury bill. The comparison of rates of return of the benchmark index and the sample of fund of funds indicated that majority of the equity fund of funds included in the sample had underperformed the benchmark. Such results might be because of double layer of fees. The results revealed that the performance of fund of funds had posted a negative Sharpe, Treynor, and Jensen alpha. The underperformance of fund of mutual funds strongly explained the double layer of fees.